Find the best solutions to your questions at Westonci.ca, the premier Q&A platform with a community of knowledgeable experts. Get expert answers to your questions quickly and accurately from our dedicated community of professionals. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.

The equation to determine the number of months Michael will have to pay on the car is [tex]\frac{1}{3}(x+7) - \frac{1}{2}(x+1) = -6[/tex], where [tex]x[/tex] represents the number of months. Find the number of months Michael will have to pay on the car.

Sagot :

To solve the equation [tex]\( \frac{1}{3(x+7)} - \frac{1}{2(x+1)} = -6 \)[/tex], where [tex]\( x \)[/tex] represents the number of months, follow these steps:

1. Rewrite the equation:
[tex]\[ \frac{1}{3(x+7)} - \frac{1}{2(x+1)} = -6 \][/tex]

2. Find a common denominator for the fractions on the left so that you can combine them. The terms are [tex]\( 3(x+7) \)[/tex] and [tex]\( 2(x+1) \)[/tex], so the common denominator is [tex]\( 6(x+7)(x+1) \)[/tex].

3. Rewrite each fraction with the common denominator:
[tex]\[ \frac{2(x+1)}{6(x+7)(x+1)} - \frac{3(x+7)}{6(x+7)(x+1)} = -6 \][/tex]

4. Combine the fractions:
[tex]\[ \frac{2(x+1) - 3(x+7)}{6(x+7)(x+1)} = -6 \][/tex]

5. Simplify the numerator:
[tex]\[ 2(x + 1) - 3(x + 7) = 2x + 2 - 3x - 21 = -x - 19 \][/tex]
So, the equation becomes:
[tex]\[ \frac{-x - 19}{6(x+7)(x+1)} = -6 \][/tex]

6. Eliminate the denominator by multiplying both sides of the equation by [tex]\( 6(x+7)(x+1) \)[/tex]:
[tex]\[ -x - 19 = -6 \cdot 6(x+7)(x+1) \][/tex]
[tex]\[ -x - 19 = -36(x^2 + 8x + 7) \][/tex]

7. Simplify the right side:
[tex]\[ -x - 19 = -36x^2 - 288x - 252 \][/tex]

8. Move all terms to one side to form a standard quadratic equation:
[tex]\[ -36x^2 - 288x - 252 + x + 19 = 0 \][/tex]
[tex]\[ -36x^2 - 287x - 233 = 0 \][/tex]
Multiply through by [tex]\(-1\)[/tex] to make the coefficients positive:
[tex]\[ 36x^2 + 287x + 233 = 0 \][/tex]

9. Solve the quadratic equation: [tex]\( 36x^2 + 287x + 233 = 0 \)[/tex]. To do this, we use the quadratic formula [tex]\( x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \)[/tex], where [tex]\( a = 36 \)[/tex], [tex]\( b = 287 \)[/tex], and [tex]\( c = 233 \)[/tex].

The solutions given in the result are already simplified and are:
[tex]\[ x = \frac{-287 - \sqrt{48817}}{72} \quad \text{and} \quad x = \frac{-287 + \sqrt{48817}}{72} \][/tex]

Therefore, the number of months Michael will have to pay on the car corresponds to the roots of this equation, which are:
[tex]\[ x = \frac{-287 - \sqrt{48817}}{72} \quad \text{and} \quad x = \frac{-287 + \sqrt{48817}}{72} \][/tex]